Similar Mechanism of Various Lupus Anticoagulants - Exner, Thomas (Thrombosis and Haemostasis, 1985)
Potent lupus inhibitors from various patients were mixed with platelet free normal plasma and were compared in activated partial thromboplastin time (APTT), dilute prothrombin time (dil. PT), kaolin clotting time (KCT), contact product clotting time (CPCT), and Russell viper venom clotting time (RWCT) tests. In the last three tests platelets and platelet lipid substitutes were avoided to enhance the sensitivities of these tests for the lupus anticoagulant. Correlations between the KCT and the other tests were mostly good, indicating that different lupus inhibitors functioned by a similar mechanism. There was no significant trend between particular clinical symptoms and individual coagulation test combinations. The KCT was found to be the most sensitive test for the lupus inhibitor, followed by the CPCT, RWCT, dil. PT and APTT tests. Activated platelets tended to correct the APTT lupus inhibitor defect in all except the strongest inhibitor cases.
Keywords: Lupus inhibitors; Mechanism; Test sensitivity; Clinical associations